46.0k views
19 votes
..vertex: (4, -1)
f(3) = -6

User Fatalize
by
5.3k points

1 Answer

8 votes

Answer:


\huge\boxed{f(x)=-5(x-4)^2-1=-5x^2+40x-81}

Explanation:

The vertex form of an equation of a parabola:


f(x)=a(x-h)^2+k


(h;\ k) - vertex

We have

vertex
(4;\ -1)\to h=4;\ k=-1


f(3)=-6

Therefore we have:


f(x)=a(x-4)^2+(-1)=a(x-4)^2-1

Substitute
x=3 and
f(3)=-6


a(3-4)^2-1=-6\qquad|\text{add 1 to both sides}\\\\a(-1)^2=-6+1\\\\a(1)=-5\\\\a=-5

Finally:


f(x)=-5(x-4)^2-1=-5(x^2-2(x)(4)+4^2)-1\\\\=-5(x^2-8x+16)-1=-5x^2+(-5)(-8x)+(-5)(16)-1\\\\=-5x^2+40x-80-1=-5x^2+40x-81

User Louisa
by
5.0k points